GAMBARAN TINGKAT PENGETAHUAN PAPARAN RADIASI GAWAI TERHADAP KESEHATAN MATA PADA MAHASISWA ANGKATAN 2020 FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - HIKMAH ISLAMI; ZALDI ZALDI (LP2MTBM MAKARIOZ, 2023)
One of the things that affects eye health is the use of gadgets, this is caused by the exposure of radiation and the impact of it. Therefore it is important to know the level of knowledge in its application, especially students as an active users of gadgets. To find out the differences in knowledge of device radiation exposure on eye health in Medical Students of 2020’s batch Muhammadiyah University, North Sumatra. The design used for this research is descriptive analytic with a cross-sectional study. This study found the sample of 150 people consisting of 75 men and 75 women. Data was obtained using questionnaire that has been distributed as many as 25 questions consisting of the level of general knowledge and the level of knowledge of factors that affect eye health, and the level of knowledge will be assessed by the results that was processed using the Statistical Package for the Social Science (SPSS) program. From 150 respondents, the overall level of knowledge was good with an overall percentage of 64.7% and it was found that there was no differences in level of knowledge between men and women which is p-value 0,86 (>0,05). Based on the results of this study it assumed that there is no differences in the level of knowledge of device radiation exposure amongs the students of the 2020’s batch of Faculty of Medicine, University Muhammadiyah North Sumatra. Keywords: Knowledge level, Radiation, Gadget, Medical student